Magnetic biochar composite adsorbent and preparation method and water treatment application thereof

By adding magnetic materials to the surface of biochar, magnetic biochar composite adsorbent is prepared, which solves the problem of difficulty in separation and recovery of traditional adsorbents, and improves the adsorption performance, achieving efficient and economical water treatment effect.

CN119549132APending Publication Date: 2025-03-04GUIZHOU MINZU UNIV
View PDF 0 Cites 6 Cited by

Patent Information

Application Number
CN202411848653.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

It is difficult to separate and recover traditional adsorbents in water treatment, and their adsorption performance needs to be improved.

Method used

By adding magnetic material to the surface of biochar, a magnetic biochar composite adsorbent is prepared, and the easy separation characteristics of the magnetic material and the high adsorption properties of biochar are utilized.

Benefits of technology

It realizes efficient recycling of adsorbents and multiple reuses, reduces processing costs, improves adsorption performance, and significantly improves the adsorption capacity of heavy metals and organic dyes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119549132A_ABST
    Figure CN119549132A_ABST
Patent Text Reader

Abstract

The invention discloses a magnetic biochar composite adsorbent as well as a preparation method and water treatment application thereof, and relates to the technical field of adsorption materials. The preparation method consists of a biochar matrix and magnetic particles loaded on the surface and in pores of the biochar matrix, and comprises the following steps: preparation of the biochar matrix: step 1, firstly, selecting a biomass raw material; the magnetic charcoal composite adsorbent has unique structure and performance advantages, abundant pore structures and surface functional groups of the adsorbent can provide a large number of adsorption sites for pollutants, and due to the existence of magnetic particles, after the adsorption process is completed, the adsorbent only needs to be placed in an external magnetic field such as an electromagnet and a permanent magnet, so that the magnetic charcoal composite adsorbent can be used for adsorbing the pollutants. The adsorbent can be rapidly separated from the solution or the suspension, the separation time can be controlled within 1-10 minutes, the recovery efficiency of the adsorbent is greatly improved, the treatment cost is reduced, and the adsorbent can be repeatedly used and has good economical efficiency and environmental protection property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adsorption materials, and in particular relates to a magnetic biochar composite adsorbent, a preparation method thereof, and water treatment applications. Background Art

[0002] In today's environmental governance field, water pollution is a major problem that needs to be solved urgently. There are various pollutants in water, including heavy metal ions (such as lead, cadmium, mercury, copper, etc.), organic pollutants (such as pesticide residues, polycyclic aromatic hydrocarbons, organic dyes, etc.) and some emerging pollutants (such as antibiotics, endocrine disruptors, etc.). These pollutants not only cause serious damage to aquatic ecosystems, but also threaten human health through the transmission of the food chain. Adsorption method, as a commonly used water treatment technology, has the advantages of simple operation, relatively low cost, and good removal effect. Traditional adsorbents such as activated carbon, although they have a high specific surface area and adsorption capacity, have the problem of difficulty in separation and recovery. Especially in large-scale water treatment applications, the separation and recovery cost of adsorbents is high and the efficiency is low, which is easy to cause secondary pollution.

[0003] Biochar is a carbon-containing material formed by the pyrolysis of biomass under oxygen-deficient or oxygen-limited conditions. It has a rich pore structure, a certain specific surface area and surface functional groups, and can adsorb a variety of pollutants. However, biochar itself has fine particles, and it is difficult to effectively separate it from the treated water in practical applications. Magnetic materials have the characteristics of being able to quickly and conveniently achieve separation under the action of an external magnetic field. The magnetic material is compounded with biochar to prepare a magnetic biochar composite adsorbent, which can fully combine the adsorption properties of biochar and the easy separation characteristics of magnetic materials, providing an effective way to solve the problem of difficult separation and recovery of traditional adsorbents, and has broad application prospects in environmental governance fields such as water treatment and soil remediation.

[0004] To this end, we provide a magnetic biochar composite adsorbent and its preparation method and water treatment application to solve the above-mentioned problems. Summary of the invention

[0005] The purpose of the present invention is to provide a magnetic biochar composite adsorbent and its preparation method and water treatment application. By adding magnetic material to the surface of biochar, the problems of difficulty in separating and recovering adsorbents in the prior art and the need to further improve adsorption performance are solved.

[0006] To solve the above technical problems, the present invention is implemented through the following technical solutions.

[0007] The present invention is a magnetic biochar composite adsorbent and a preparation method thereof, which is composed of a biochar matrix and magnetic particles loaded on its surface and in its pores, and comprises the following steps: preparation of the biochar matrix: step 1, first, select biomass raw materials, such as agricultural waste, including but not limited to corn stalks, wheat stalks, rice husks, forestry waste, wood chips, branches and urban organic waste, discarded wooden furniture, paper; step 2, pre-treat the biomass raw materials, first wash them to remove surface impurities, and after drying, use a pulverizer to crush them to a suitable particle size, generally 1-10 mm; step 3, place the crushed biomass raw materials in an inert gas-protected pyrolysis device for pyrolysis; step 4, during the pyrolysis process, the organic matter inside the biomass raw materials gradually decomposes and volatilizes to form a rich pore structure, and at the same time certain functional groups are generated on the surface, and finally converted into a biochar matrix with a pore structure and certain surface functional groups, and its specific surface area can reach 100-500 square meters / gram; the ferromagnetic material ferroferric oxide is used to prepare ferroferric oxide magnetic particles by co-precipitation method The specific preparation steps are as follows: A. First, prepare a ferric chloride solution and a ferrous chloride solution with a concentration of 0.5-2 mol / L respectively, and mix the ferric chloride solution and the ferrous chloride solution in a molar ratio of 1.5-2.5:1 to obtain a mixed iron salt solution; B. During the stirring process, slowly drop an alkaline solution with a concentration of 2-6 mol / L into the mixed iron salt solution, and control the dropping speed so that the pH value of the reactant is always maintained between 8 and 11. With the dropwise addition of the alkaline solution, a black precipitate is gradually generated in the solution to generate trioxide tetroxide. Ferromagnetic particles; C. After the reaction is completed, the generated magnetic particles are quickly separated from the solution by an external magnetic field, and then repeatedly washed with deionized water for 3-5 times to remove the impurity ions remaining on the surface of the particles. After drying, dry ferroferric oxide magnetic particles are obtained for standby use; D. The prepared biochar matrix is ​​added to a solution containing a magnetic particle precursor, and the magnetic particle precursor is evenly dispersed on the surface and pores of the biochar matrix by stirring and ultrasound, and then a reaction is carried out to generate magnetic particles in situ on the biochar matrix.

[0008] The present invention is further configured such that, in the step 2, the biomass raw material is dried at 60-120° C. for 12-48 hours to remove moisture.

[0009] The present invention is further configured such that, in the step three, the pyrolysis temperature of the biomass raw material is controlled at 300-700°C, the pyrolysis time is 1-5 hours, and the heating rate is 5-20°C / minute.

[0010] The present invention is further configured such that in step B, the reaction process is carried out at a temperature range of room temperature to 60° C., and the reaction time lasts for 30-120 minutes.

[0011] The present invention is further configured such that, in the step C, the washed magnetic particles are dried at 60-100° C. for 12-24 hours.

[0012] The present invention is further configured such that in the step D, the prepared biochar matrix is ​​added to a solution containing a magnetic particle precursor at a mass volume ratio of 1:10-1:50 (g / mL), and first stirred at a speed of 200-500 rpm for 30-60 minutes to uniformly disperse the biochar matrix in the solution and initially contact the magnetic particle precursor.

[0013] The present invention is further configured such that in step D, the mixture is placed in an ultrasonic generator and ultrasonically treated for 20-60 minutes at an ultrasonic power of 200-800 watts, and the cavitation effect of the ultrasound is used to enable the magnetic particle precursor to penetrate into the pores of the biochar matrix and adhere to its surface.

[0014] The present invention is further configured that in the step D, after the ultrasonic treatment is completed, the mixture is stirred and reacted at a temperature of 30-60°C for 1-3 hours to generate magnetic particles in situ on the biochar matrix. After the reaction is completed, the magnetic biochar composite adsorbent is separated from the solution by an external magnetic field, and repeatedly washed with deionized water for 3-5 times to remove unreacted precursors and other impurities, and finally dried at 60-100°C for 12-24 hours to obtain a magnetic biochar composite adsorbent.

[0015] A water treatment application of a magnetic biochar composite adsorbent. When adsorbing heavy metal ions, the magnetic biochar composite adsorbent is added to an aqueous solution containing heavy metal ions, the adsorbent dosage is 0.5-5g / L, the solution pH value is adjusted to 4-7, and oscillation adsorption is performed at room temperature for 30-120 minutes. The adsorption capacity of the adsorbent for lead ions can reach 100-200mg / g, and the adsorption capacity for mercury ions can reach 80-150mg / g.

[0016] The present invention is further configured that, when adsorbing organic dyes, the adsorbent dosage is 1-10 g / L, the solution pH is adjusted to 3-8, the oscillation adsorption time is 60-180 minutes, the adsorption capacity for methylene blue can reach 50-120 mg / g, and the adsorption capacity for rhodamine B can reach 40-100 mg / g.

[0017] The present invention has the following beneficial effects.

[0018] 1. The magnetic biochar composite adsorbent of the present invention has unique structural and performance advantages. Its rich pore structure and surface functional groups can provide a large number of adsorption sites for pollutants. Due to the presence of magnetic particles, after the adsorption process is completed, the adsorbent only needs to be placed in an external magnetic field, such as a magnetic field generated by an electromagnet, a permanent magnet, etc., and the adsorbent can be quickly separated from the solution or suspension. The separation time can be controlled within 1-10 minutes, which greatly improves the recovery efficiency of the adsorbent and reduces the processing cost. It can be reused many times and has good economy and environmental protection.

[0019] 2. The raw materials of the present invention are widely available and the preparation process is relatively simple. The raw materials of the biochar matrix can be selected from a variety of common biomass wastes, such as agricultural and forestry wastes and urban organic waste. These raw materials are sufficient in source and low in cost, which is conducive to the resource utilization of wastes. At the same time, although the preparation process of the magnetic biochar composite adsorbent involves multiple steps, the conditions of each step are relatively mild and easy to control, and do not require complex and expensive equipment, which is convenient for industrial large-scale production and promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the drawings required for describing the embodiment are briefly introduced below.

[0021] Figure 1 The present invention discloses a magnetic biochar composite adsorbent, a preparation method thereof and a flow chart of biochar preparation for water treatment application.

[0022] Figure 2 The present invention is a magnetic biochar composite adsorbent, a preparation method thereof and a preparation flow chart of magnetic particles for water treatment applications.

[0023] Figure 3 The present invention provides a magnetic biochar composite adsorbent and a preparation method thereof, as well as a preparation flow chart of the magnetic biochar composite adsorbent in water treatment applications. DETAILED DESCRIPTION

[0024] The technical solutions in the embodiments of the present invention will be described below in conjunction with the drawings in the embodiments of the present invention. The described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0025] Embodiment 1

[0026] The present invention is a magnetic biochar composite adsorbent and a preparation method thereof, comprising a biochar matrix and magnetic particles loaded on its surface and in its pores, and comprising the following steps: preparation of the biochar matrix: step 1, first, select biomass raw materials, such as agricultural waste, including but not limited to corn stalks, wheat stalks, rice husks, forestry waste, wood chips, branches and urban organic waste, discarded wooden furniture, paper; step 2, pre-treat the biomass raw materials, first wash them to remove surface impurities, and after drying, grind them into a suitable particle size, generally 1-10 mm, by a grinder; step 3, place the crushed biomass raw materials in an inert gas-protected pyrolysis device for pyrolysis; step 4, during the pyrolysis process, the organic matter inside the biomass raw materials gradually decomposes and volatilizes to form a rich pore structure, and at the same time certain functional groups are generated on the surface, and finally converted into a biochar matrix with a pore structure and certain surface functional groups, and its specific surface area can reach 100-500 square meters / gram; ferromagnetic material ferroferric oxide is used to prepare ferroferric oxide magnetic adsorbent by co-precipitation method The particles are prepared in the following specific steps: A. firstly prepare a ferric chloride solution and a ferrous chloride solution with a concentration of 0.5-2 mol / L respectively, and mix the ferric chloride solution and the ferrous chloride solution in a molar ratio of 1.5-2.5:1 to obtain a mixed iron salt solution; B. during the stirring process, slowly drop an alkaline solution with a concentration of 2-6 mol / L into the mixed iron salt solution, and control the dropping speed so that the pH value of the reactant is always maintained between 8 and 11. With the dropwise addition of the alkaline solution, a black precipitate is gradually generated in the solution to generate tetraoxide. ferromagnetic particles; C. After the reaction is completed, the generated magnetic particles are quickly separated from the solution by an external magnetic field, and then repeatedly washed with deionized water for 3-5 times to remove the impurity ions remaining on the surface of the particles. After drying, dry ferroferric oxide magnetic particles are obtained for later use; D. The prepared biochar matrix is ​​added to a solution containing a magnetic particle precursor, and the magnetic particle precursor is evenly dispersed on the surface and pores of the biochar matrix by stirring and ultrasound, and then a reaction is carried out to generate magnetic particles in situ on the biochar matrix.

[0027] Embodiment 2

[0028] In step 2, the biomass raw material is dried at 60-120°C for 12-48 hours to remove moisture. In step 3, the pyrolysis temperature of the biomass raw material is controlled at 300-700°C, the pyrolysis time is 1-5 hours, and the heating rate is 5-20°C / minute. In step B, the reaction process is carried out in a temperature range from room temperature to 60°C, and the reaction time lasts for 30-120 minutes. In step C, the washed magnetic particles are dried at 60-100°C for 12-24 hours. In step D, the prepared biochar matrix is ​​added to the solution containing the magnetic particle precursor according to a mass volume ratio of 1:10-1:50 (g / mL), and first stirred at a speed of 200-500 rpm for 30-60 minutes to uniformly disperse the biochar matrix in the solution. And initially contact with the magnetic particle precursor. In step D, the mixture is placed in an ultrasonic generator and ultrasonically treated for 20-60 minutes at an ultrasonic power of 200-800 watts. The cavitation effect of the ultrasound is used to enable the magnetic particle precursor to penetrate into the pores of the biochar matrix and adhere to its surface. In step D, after the ultrasonic treatment is completed, the mixture is stirred and reacted at a temperature of 30-60°C for 1-3 hours to allow the magnetic particles to be generated in situ on the biochar matrix. After the reaction is completed, the magnetic biochar composite adsorbent is separated from the solution by an external magnetic field, and repeatedly washed with deionized water for 3-5 times to remove unreacted precursors and other impurities. Finally, it is dried at 60-100°C for 12-24 hours to obtain the magnetic biochar composite adsorbent.

[0029] Embodiment 3

[0030] Take corn stalks, clean them, dry them at 105°C to constant weight, crush them to a particle size of 2-5 mm, put them into a tubular furnace, and heat them to 500°C at a heating rate of 10°C / min under nitrogen protection, and pyrolyze them for 3 hours to obtain a biochar matrix.

[0031] The coprecipitation method was used to prepare ferroferric oxide magnetic particles. A ferric chloride solution and a ferrous chloride solution with a concentration of 1 mol / L were prepared respectively, and the mixed iron salt solution was obtained by mixing them in a molar ratio of 2:1. Under stirring, a sodium hydroxide solution with a concentration of 4 mol / L was slowly added dropwise to the mixed iron salt solution. The pH value of the reaction body was maintained at 10. The reaction was carried out at 40°C for 60 minutes. After the reaction was completed, the magnetic particles were separated by a magnetic field, washed with deionized water 4 times, and dried at 80°C for 18 hours.

[0032] 10 grams of biochar matrix was added to the above solution containing magnetic particles at a mass-to-volume ratio of 1:30 (g / mL), first stirred at a speed of 300 rpm for 45 minutes, and then ultrasonically treated for 40 minutes at an ultrasonic power of 500 watts. After the ultrasonic treatment, stirring was continued at 45°C for 2 hours. After the reaction, it was repeatedly washed with deionized water until neutral, and then dried at 80°C to constant weight to obtain a magnetic biochar composite adsorbent, in which the loading amount of magnetic particles was about 30% (mass fraction).

[0033] The adsorbent was used to treat an aqueous solution containing a lead ion concentration of 100 mg / L. The adsorbent dosage was 2 g / L, the solution pH was adjusted to 6, and oscillation adsorption was carried out at room temperature for 60 minutes. After the adsorption was completed, the adsorbent was separated using an external magnetic field, and the lead ion concentration in the solution was measured. The adsorption capacity was calculated to be 150 mg / g.

[0034] Embodiment 4

[0035] Wheat straw was selected as the biomass raw material for pyrolysis, and the pyrolysis conditions were: heating rate 15°C / min, pyrolysis temperature 600°C, and pyrolysis time 4 hours.

[0036] The ferroferric oxide magnetic particles were prepared by a co-precipitation method, and the biochar matrix was reacted with the magnetic particle solution to prepare a composite adsorbent, and the magnetic particle loading was about 40% (mass fraction).

[0037] The adsorbent was used to treat an aqueous solution containing a mercury ion concentration of 80 mg / L. The adsorbent dosage was 3 g / L, the solution pH was adjusted to 5, and oscillation adsorption was performed for 120 minutes. After the adsorption was completed, the adsorbent was separated by a magnetic field and the mercury ion concentration was measured, and the adsorption capacity was found to be 180 mg / g.

[0038] Embodiment 5

[0039] Rice husk was taken as the biomass raw material, which was cleaned, dried at 100°C for 24 hours, and then crushed to a particle size of 3-6 mm. It was placed in a nitrogen-protected tubular furnace, heated to 450°C at a heating rate of 8°C / min, and pyrolyzed for 2.5 hours to obtain a biochar matrix.

[0040] A 1.5 mol / L ferric chloride solution and a 0.75 mol / L ferrous chloride solution were prepared to form a mixed iron salt solution, a 3 mol / L sodium hydroxide solution was slowly added dropwise under stirring, the pH value was controlled at 9-10, and the mixture was reacted at 35° C. for 90 minutes to prepare ferrosoferric oxide magnetic particles, which were separated by a magnetic field, washed, and dried at 70° C. for 16 hours.

[0041] 8 grams of biochar matrix was added to the magnetic particle solution at a mass-to-volume ratio of 1:20 (g / mL), first stirred at 300 rpm for 50 minutes, ultrasonicated at 400 watts for 30 minutes, and then stirred at 50°C for 1.5 hours. After the reaction, the magnetic biochar composite adsorbent was separated, washed, and dried at 90°C for 18 hours. The magnetic particle loading was about 35%.

[0042] This adsorbent was used to treat an aqueous solution containing a cadmium ion concentration of 80 mg / L, with a dosage of 2.5 g / L and a pH value adjusted to 5.5. It was adsorbed at 25°C and 200 rpm for 90 minutes. After the adsorption was completed, it was separated by a magnetic field and the cadmium ion concentration was measured. The adsorption capacity was calculated to be approximately 130 mg / g.

[0043] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that technicians in the relevant technical field can better understand and utilize the present invention.

Claims

1. A magnetic biochar composite adsorbent and a preparation method thereof, comprising a biochar matrix and magnetic particles loaded on the surface and in the pores thereof, characterized in that: The following steps are involved: Preparation of biochar matrix: Step 1: First, select biomass raw materials, such as agricultural waste, including but not limited to corn stalks, wheat straw, rice husks, forestry waste, wood chips, branches, and urban organic waste, discarded wooden furniture, and paper; Step 2: pre-treat the biomass raw materials by washing them to remove surface impurities, drying them, and then crushing them into appropriate particle sizes, generally 1-10 mm, using a crusher; Step 3: placing the crushed biomass raw material in a pyrolysis device protected by inert gas for pyrolysis; Step 4: During the pyrolysis process, the organic matter inside the biomass raw material gradually decomposes and volatilizes to form a rich pore structure, and certain functional groups are generated on the surface, and finally converted into a biochar matrix with a pore structure and certain surface functional groups, and its specific surface area can reach 100-500 square meters / gram; The ferromagnetic material ferroferric oxide is used to prepare ferroferric oxide magnetic particles by a coprecipitation method. The specific preparation steps are as follows: A. First, prepare a ferric chloride solution and a ferrous chloride solution with a concentration of 0.5-2 mol / L respectively, and mix the ferric chloride solution and the ferrous chloride solution in a molar ratio of 1.5-2.5:1 to obtain a mixed iron salt solution; B. During the stirring process, slowly drop an alkaline solution with a concentration of 2-6 mol / L into the mixed iron salt solution, and control the dropping speed so that the pH value of the reactant is always maintained between 8 and 11. As the alkaline solution is added, a black precipitate gradually forms in the solution, generating ferroferric oxide magnetic particles; C. After the reaction is completed, the generated magnetic particles are quickly separated from the solution by using an external magnetic field, and then washed repeatedly with deionized water for 3-5 times to remove the impurity ions remaining on the surface of the particles. After drying, dry ferroferric oxide magnetic particles are obtained for standby use; D. Add the prepared biochar matrix to a solution containing a magnetic particle precursor, and evenly disperse the magnetic particle precursor on the surface and pores of the biochar matrix by stirring and ultrasonication, and then react to generate magnetic particles in situ on the biochar matrix.

2. The magnetic biochar composite adsorbent and the preparation method thereof according to claim 1, characterized in that: In the step 2, the biomass raw material is dried at 60-120° C. for 12-48 hours to remove moisture.

3. The magnetic biochar composite adsorbent and the preparation method thereof according to claim 1, characterized in that: In the step 3, the pyrolysis temperature of the biomass raw material is controlled at 300-700°C, the pyrolysis time is 1-5 hours, and the heating rate is 5-20°C / minute.

4. The magnetic biochar composite adsorbent and the preparation method thereof according to claim 1, characterized in that: In the step B, the reaction process is carried out at a temperature ranging from room temperature to 60° C., and the reaction time lasts for 30-120 minutes.

5. The magnetic biochar composite adsorbent and the preparation method thereof according to claim 1, characterized in that: In the step C, the washed magnetic particles are dried at 60-100° C. for 12-24 hours.

6. The magnetic biochar composite adsorbent and the preparation method thereof according to claim 1, characterized in that: In the step D, the prepared biochar matrix is ​​added to the solution containing the magnetic particle precursor at a mass volume ratio of 1:10-1:50 (g / mL), and first stirred at a speed of 200-500 rpm for 30-60 minutes to uniformly disperse the biochar matrix in the solution and initially contact the magnetic particle precursor.

7. The magnetic biochar composite adsorbent and the preparation method thereof according to claim 1, characterized in that: In the step D, the mixture is placed in an ultrasonic generator and ultrasonically treated for 20-60 minutes at an ultrasonic power of 200-800 watts, so that the magnetic particle precursor can penetrate into the pores of the biochar matrix and adhere to its surface by utilizing the cavitation effect of the ultrasound.

8. The magnetic biochar composite adsorbent and the preparation method thereof according to claim 1, characterized in that: In the step D, after the ultrasonic treatment is completed, the mixture is stirred and reacted at a temperature of 30-60° C. for 1-3 hours to generate magnetic particles in situ on the biochar matrix. After the reaction is completed, the magnetic biochar composite adsorbent is separated from the solution by an external magnetic field, and repeatedly washed with deionized water for 3-5 times to remove unreacted precursors and other impurities, and finally dried at 60-100° C. for 12-24 hours to obtain the magnetic biochar composite adsorbent.

9. The water treatment application of a magnetic biochar composite adsorbent according to any one of claims 1 to 8, characterized in that: When adsorbing heavy metal ions, the magnetic biochar composite adsorbent is added to an aqueous solution containing heavy metal ions, the adsorbent dosage is 0.5-5g / L, the solution pH is adjusted to 4-7, and oscillation adsorption is carried out at room temperature for 30-120 minutes. The adsorption capacity of the adsorbent for lead ions can reach 100-200mg / g, and the adsorption capacity for mercury ions can reach 80-150mg / g.

10. The water treatment application of a magnetic biochar composite adsorbent according to any one of claims 1 to 8, characterized in that: When adsorbing organic dyes, the adsorbent dosage is 1-10 g / L, the solution pH is adjusted to 3-8, the oscillation adsorption time is 60-180 minutes, the adsorption capacity for methylene blue can reach 50-120 mg / g, and the adsorption capacity for rhodamine B can reach 40-100 mg / g.

Citation Information

Cited By

  • Slurry dehydration method based on cooperation of carbon-silicon skeleton regulation and multi-mechanism compound flocculation

    CN120518307A

  • O-nitroaniline wastewater treatment method

    CN120794241A

  • Magnetic biochar as well as preparation method and application thereof

    CN120860996A

  • Carbon-based adsorption material for groundwater remediation and preparation method of carbon-based adsorption material

    CN121571118A

  • Efficient concentration process for waste acid generated in production of phenylenediamine

    CN121672877A